+0  
 
0
90
1
avatar

If g(x) = (x + 3)/4, for what value of x will g(2x) = 2(g(x)) ? Express your answer in simplest form.

 Jan 12, 2022
 #1
avatar+23183 
+1

g(x)  =  (x + 3)/4     --->     g(2x)  =  (2x + 3)/4

 

g(x)  =  (x + 3)/4     --->     2( g(x) )  =  2( (x + 3)/4 )  =  (x + 3)/2

 

g(2x)  =  2( g(x) )     --->     (2x + 3)/4  =  (x + 3)/2

   (multiply by 4)                    (2x + 3)  =  2(x + 3)

                                                2x + 3  =  2x + 6

                                                        3  =  6                    <---  Impossible!  No value works.

 Jan 13, 2022

12 Online Users

avatar